Checks and Balances in Utility Regulation The U.K. Experience - Green, Richard (World Bank, Washington, DC, 2012)
In the United States the courts have long been involved in the oversight of regulators. In the United Kingdom, which created its utility regulators from scratch in the 1980s, an alternative system was sought. This system centers on three concerns: the procedure followed by the regulator, the substance of the decisions, and the acceptability of the decisions to the public. Three main institutions have oversight roles: the Competition Commission (formerly the Monopolies and Mergers Commission), parliamentary select committees, and the courts. This Note reviews the roles of these institutions.